2020
DOI: 10.1002/cre2.298
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic factors influencing dimensions of soft tissue graft from the hard palate. A clinical study

Abstract: Objectives The aim of the present study was to measure the thickness of the palatal mucosa in a Jordanian (Middle Eastern) population as well as identify possible factors that may influence the thickness of palatal mucosa. Material and Methods Sixty period on tally healthy subjects (29 males and 31 females) were selected. Fifteen measurement points were defined on the palate. The mucosal thickness in the hard palate was determined by “bone sounding” with a Hu‐Friedy® round periodontal probe. Results The overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
0
9
1
3
Order By: Relevance
“…The most appropriate area for graft harvesting is the canine-premolar area, 8–13 mm from the midpalatal aspect of each respective tooth. At this position, there less risk of endangering the greater palatine bundle but with an inherent risk of an aesthetic unacceptable outcome, particularly in free gingival grafts, due to the presence of the rugae [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most appropriate area for graft harvesting is the canine-premolar area, 8–13 mm from the midpalatal aspect of each respective tooth. At this position, there less risk of endangering the greater palatine bundle but with an inherent risk of an aesthetic unacceptable outcome, particularly in free gingival grafts, due to the presence of the rugae [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings revealed that 90.5% of the rugae reached the upper second premolar and 88.3% extended beyond its mesial aspect. So, basically, the rugae zone extended to the upper second premolar area which poses a problem, as the premolar area in the Jordanian population is the most appropriate donor graft area [ 36 ]. The problem is further complicated by the rugae extending as far back as the premolars, not only mesiodistally but also mediolateraly, indicating that it extended very close to the median palatine raphe posteriorly in most of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…The preferred place to harvest grafts is from the canine-premolar region, 8-13 mm from the midpalatal face of each tooth [34]. The greater palatine bundle is less at risk in this location; however, the presence of the rugae increases the chance of an undesirable cosmetic result, especially with free gingival grafts [34]. There is not much information about the effect of transplanting tissue from the rugae-containing anterior palate.…”
Section: Discussionmentioning
confidence: 99%
“…Có sự khác nhau về kết quả giữa các nghiên cứu, có thể là do sự khác nhau về chủng tộc, số lượng mẫu nghiên cứu, độ tuổi của mẫu nghiên cứu và phương pháp đo niêm mạc khẩu cái được sử dụng trong mỗi nghiên cứu. Không có sự khác biệt về độ dày niêm mạc giữa bên phải và bên trái, kết quả này tương tự với nghiên cứu của Barriviera và cộng sự, Said và cộng sự [1], [10].…”
Section: độ Dày Niêm Mạc Khẩu Cái Cứng Của Người Việt Trưởng Thànhunclassified
“…-Nam và nữ: Kết quả này phù hợp với các nghiên cứu Barriviera và cộng sự, Said và cộng sự, Yaman và cộng sự [1], [10], [14]. Nghiên cứu của Kuriakose và cộng sự, Song và cộng sự cho thấy nữ giới có độ dày nhỏ hơn nam giới có ý nghĩa thống kê [8], [13].…”
Section: đáNh Giá Sự Liên Quan Một Số Yếu Tốunclassified